KEBIJAKAN PENATAAN DAN PEMELIHARAAN PASAR RAKYAT/ PASAR INDUK KABUPATEN BIREUEN - Octriani, Santi; Akmal, Muhammad; Muklir, Muhammad (Program Magister Administrasi Publik, 2022)
The Cureh Main Market is the main market in Bireun Regency which is the center of the sub-district markets that operate from morning to evening and even late at night, but this does not happen in the Cureh Main Market, as is the phenomenon that has occurred until now people prefer shopping at the Meunasah Capa Morning Market, namely markets around settlements near people's homes as well as modern markets or online ordering, if this problem is not handled quickly, the Cureh Main market cannot last long in Bireun district. This study uses a qualitative method, in which qualitative data analysis is carried out interactively and is carried out continuously until it is complete, so that the data is saturated. The research results obtained are: 1. Cureh Main Market Arrangement and Maintenance Policy Reviewing the Market Management Administration System using three elements of content of policy from Grindle's theory. 2. Obstacles that occur so that the Cureh Main Market is not yet functioning optimally are reviewed with internal and external constraints, namely a. Internal constraints are caused by factors related to strategic locations in selling as well as the importance of knowledge and skills, as well as market conditions that greatly affect customers with muddy market conditions and flooded roads making the location look dirty and garbage scattered following the puddles which makes customers reluctant to go to the market during the rainy season. b. External constraints are caused by factors that there is no solution to avoid conflicts, as well as the rapid competition that is currently emerging with many people shopping and ordering food and vegetables, which can now be ordered using an online application. The suggestion that the author hopes is that the government and all traders work together and can continuously maximize the strategy for structuring and maintaining the Bireuen Regency Main Market, both administratively and revitalizing the construction of facilities and infrastructure of the Bireuen Regency Main Market